Minorities, scarcity and conflict - Jimenez, Antonio Montanes; Marinelli, Camila Ferreira; Pipyron, Stavroula (London Routledge, 2026)
This volume places scarcity as a defining aspect of minorities' experience and as a tool to comprehend ongoing and unresolved societal friction and global environmental challenges, strategies for survival and reproduction of the status quo, and aspirational desires for social mobility. The book is an experimental collective intellectual project departing from conventional approaches to scarcity solely as a resource-based economic or demographic concept.